Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1620/tjem.201.165
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Acute Exercise on Urinary Protein, Creatinine, Insulin-Like Growth Factor-I (IGF-I) and IGF Binding Protein-3 Concentrations in Children

Abstract: Insulin-like growth factor-I (IGF-I) is a polypeptide hormone and present in human urine. Insulin-like growth factor binding protein-3 (IGFBP-3) is the major form of binding protein in human circulation and functions as a carrier for IGF-I. Our goal was to determine the effects of volleyball exercise on the concentrations of urine protein, creatinine, IGF-I, and IGFBP-3 in children and to find out whether these effects differ between boys and girls. Volunteer children (13 females and 14 males), aged 10-13 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
1
12
0
2
Order By: Relevance
“…Plasma IGF-I response to physical exercise has not been demonstrated consistently; some research groups have observed increments, while others showed no variations (Di Luigi et al 1997;Nguyen et al 1998;Wallace et al 1999;Turgut et al 2003). This may be due to the different type and duration of the performance and training conducted.…”
Section: Discussionmentioning
confidence: 98%
“…Plasma IGF-I response to physical exercise has not been demonstrated consistently; some research groups have observed increments, while others showed no variations (Di Luigi et al 1997;Nguyen et al 1998;Wallace et al 1999;Turgut et al 2003). This may be due to the different type and duration of the performance and training conducted.…”
Section: Discussionmentioning
confidence: 98%
“…Se os sujeitos se encontram em um estado hipohidratado, a proteína é excretada devido à diminuição do volume plasmático. A proteína presente na urina também acontece devido ao estresse causado pelo exercício e parece ser induzida por um aumento no sangue de ácidos, que levam a alterações na molécula de albumina 14 . Talvez a intensidade do treinamento de ciclismo indoor não tenha provocado um grande estresse fisiológico, pois a FC e a PSE apresentaram um comportamento em níveis moderados até 30-35 minutos de treinamento, só após este tempo apresentaram elevações significativas (FC: >85%; PSE: >13).…”
Section: Discussionunclassified
“…Existe uma relação do nível de proteinúria e o estado de hidratação do indivíduo, sendo que a presença de proteínas na urina tende a ser maior de acordo com o aumento do grau de desidratação 14 .…”
Section: Introductionunclassified
“…The serum IGF-I level would be a better reliable indicator for screening of acromegaly, because it reflects overall GH secretion during the previous 24 h ( Thorner et al 1998). However, the normal range for serum IGF-I levels varies with age and gender, and should be corrected for them (Turgut et al 2003). Furthermore, IGF-I level also reflects the liver function and the nutrition status.…”
Section: © 2005 Tohoku University Medical Pressmentioning
confidence: 99%